Tackling dementia in patients with Parkinson's disease. - Rolinski, M; Ebmeier, K (2011)
Dementia more than one year after the onset of motor features associated with Parkinson's disease is defined as Parkinson's disease with dementia (PDD). If it develops within one year of the motor features, the term dementia with Lewy bodies (DLB) is used. Since clinical and pathological features are similar, it is generally accepted that both represent a continuum of the same disorder. PDD together with DLB account for around one fifth of all cases of dementia in the elderly. Studies suggest that most patients with Parkinson's disease would eventually develop dementia if they lived long enough. The diagnosis of PDD in the presence of long-standing pronounced motor features rarely poses a diagnostic dilemma. However, the diagnosis of DLB may be more difficult. It relies on the revised consensus clinical criteria which require the presence of at least two of the following three syndromes: persistent visual hallucinations, fluctuating defects in cognitive and functional ability, and parkinsonism. An early referral to a specialist clinic may not only help to confirm the diagnosis, but also to co-ordinate the group of professionals working with the patient. Well lit rooms and the use of glasses and hearing aids can help to reduce hallucinations. Cholinesterase inhibitors used in Alzheimer's disease have a role in DLB and PDD. Trials show moderate improvements in cognitive function in patients treated with rivastigmine. The greatest impact, however, seems to be on the psychotic features of the disease. Patients with DLB are less likely to have a good motor response from L-dopa than patients with Parkinson's disease or PDD.